On the Concept of Procedural Responsibility: General Theoretical Analysis - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2023)
This article examines the concept of procedural responsibility. The position is defended according to which procedural responsibility is interpreted not as a type of legal responsibility, but as a complex legal institution consisting of the norms of both substantive and procedural law. In turn, procedural responsibility is divided into a number of sub-institutions, including criminal procedural responsibility, which is analyzed in more or less detail.